The relationship between transformational leadership and entrepreneurial performance A study on a sample of service sector institutions of Khartoum State 2022 - Mohamed, Hassan Abdelrahmim Fadul; Mohammed, Elsheikh Mohammed Elkhidir; Souissi, Anis Mohammed; Madkhali, Huthayfah Hadi (Journal of Economic, Administrative and Legal Sciences, 2023)
The purpose of this study is to investigate the relationship between transformational leadership and entrepreneurial performance in the service sector of Khartoum State. The study used descriptive method analysis, and to meet its objectives, a survey questionnaire was designed to collect its primary data focusing on leaders of the service sector in Khartoum State. The study used improbability sample and out of 300 questionnaires distributed, 298 responses were received, representing 99% response rate. To analyse the data, (SPSS) and equation structural modelling (ESM) were used. The findings revealed that there is a partial significant relationship between transformational leadership dimensions and entrepreneurial performance dimensions (advance planning, entrepreneurial indicator, effectiveness). Accordingly, the study presented a number of recommendations, including the development of the dimensions of transformational leadership in service sector organisations, as it plays an important role within these institutions, in order to further develop the entrepreneurial performance.